Makna Kober Ganapati dalam Upacara Rsi Gana dan Upacara Nangluk Mrana : Studi Komperatif Nilai Nendidikan Teologi Hindu - Kadek Sudiana Saputra; I Wayan Budha; I Gusti Ngurah Rai (Jurnal PASUPATI, 2020)
This study will discuss the meaning of the use of Kober Gaṇapati (flag that portrays of the god Gaṇeśa) at the Ṛṣi Gaṇa ceremony held at Agung Taman Sari Temple, Halim Perdana Kusuma, and Kober Gaṇapati during the nangluk mrana ceremony held at Pura Segara Kemayu, North Jakarta. This study uses qualitative descriptive method, researchers interviewed several speakers as data, observations were made during the ceremony, by observing each series of ceremonies carried out. The results of the study prove that there is a broad meaning and value of theological education (knowledge of God) on the Kober Gaṇapati used in both ceremonies, by examining the two forms of Kober Gaṇapati, the researchers prove that there are comparison, similarities and differences in the meaning of Kober Gaṇapati. In Gaṇapati Kober, the priority is worship of the god Gaṇapati, but in the use of kober there is a difference that is the symbol used. The Kober Gaṇapati research was performed by Ṛṣi Gaṇa, the symbol of Gaṇesha carrying a gun, while at the nangluk mrana simbol kober ceremony, Gaṇapati carried chakras and mace. From the second Kober Gaṇapati the researcher proved the educational value of Hindu theology, namely the value of Nirguṇa Brahmān and Saguna Brahmān education.